INNOVATIVE PUBLIC PERSONNEL POLICY IN THE EDUCATIONAL SYSTEM OF RUSSIA (PRESENT IMPERATIVES) - T. V. Modyanova (Модернизация, инновация, развитие, 2016)
The essence of the current personnel policies in the education sphere of Russia is discussed along with the genesis of its imperatives formed under the influence of modern educational doctrine in Russia. On the basis of critical analysis, main trends shaping the global education space are shown, basic imperatives of the future human resource policy in Russia are described.